Implementation of Bandung Management System Policy Performance in the Agency for Personnel and Human Resource Development Bandung City, West Java Province: Implementation of Bandung Management - Elvis Simangunsong (Fakultas Politik Pemerintahan, 2025)
The assessment of civil servants continues to improve. The government is trying to present an objective, transparent and accountable employee performance appraisal system. The use of technology is a solution to overcome the problem of employee performance appraisal. Electronic performance remuneration is a system issued by the Bandung City government to conduct performance appraisals. In researching this problem, the researcher uses Edwards III theory to solve the problem. The research design used was qualitative with a descriptive method through an inductive approach. Data collection techniques used are interviews, and documentation. Data analysis techniques include data reduction, data display, and conclusions or verification. The results of the research conducted that Electronic Remuneration Performance in its implementation has been going well but in its implementation there are several indicators that have not been maximized. In the communication indicator, there are problems with the transmission sub-indicator. The resource indicator has been fulfilled, marked by a change in the employee's work ethic, but the sub-indicator of employee understanding is still not fulfilled. The Disposition Indicator has been running well. The bureaucratic structure has worked well and has not become an obstacle to the implementation of electronic performance remuneration. The advice given by the researcher is to conduct periodic socialization of the performance remuneration electronic system and assistance for employees in the implementation of the performance remuneration electronic system to improve employee understanding.